DISSENTING OPINION HAKIM PTUN MAKASSAR DALAM MEMUTUS PERKARA PERSPEKTIF SIYASAH SYAR’IAH - Kurniawan, Rahmat; Rahmiati (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
This study aims to understand the concept of dissenting opinion from the point of view of the Judge of the Makassar State Administrative Court and to find out the position of the dissenting opinion in the final decision and how the form of the dissenting opinion is in the perspective of Siyasah Syar'iah. The problem in this study is that the position of dissenting opinion is not clearly regulated in the system of laws and regulations in Indonesia where as a rule of law all actions that exist must be regulated clearly and specifically in laws and regulations. This research is a qualitative research (field research) with a juridical and normative syar'i approach. Primary and secondary data sources such as: results of interviews conducted at the State Administrative Court, books, case files of the State Administrative Court, scientific journals. The results of this study are 1) The concept of dissenting opinion is a different opinion from judges who have a minority voice, which occurs because the views and analysis of each judge are different. 2) The position of dissenting opinion is jurisprudence, namely as literature or reference if there are similar cases. The position of dissenting opinion is not clearly regulated in laws and regulations because basically dissenting opinion is considered not to conflict with existing laws and regulations. 3) The form of dissenting opinion in the perspective of sharia judges' siyasa is ijtihad from or maximum effort in producing sharia laws from their foundations through serious and in-depth thought and research